Peak to Average Power Ratio Reduction Using the Clipping Technique in Orthogonal Frequency Division Multiplexing System - Wan Hasan, Wan Hafiza (2006)
The demand for high-speed mobile wireless communications is rapidly growing. The orthogonal frequency division multiplexing (OFDM) technology promises to be a key technique for achieving the high data capacity and spectral efficiency requirements for wireless communication systems of the near future. With its natural resistance to multipath fading and its capability to support extremely high data rates, OFDM is a major candidate for a fourth generation system. Despite many advantages of OFDM, it has two major drawbacks which are high peak to average power ratio (PAPR) and synchronization problem. A high PAPR causes saturation in power amplifiers, leading to intermodulation products among the sub carriers and disturbing out of band energy. Therefore, it is desirable to reduce the PAPR by means of PAPR reduction schemes.Clipping has been identified as the simplest yet effective technique of PAPR reduction. However, we have found out that clipping has resulted in the degradation of BER and enhanced the growth of out of band radiation leading to the degradation of the OFDM overall performance. As a solution, we have proposed an enhanced OFDM system with the objectives of reducing the high PAPR values while minimizing the effects of clipping. The convolutional coding scheme is incorporated into the proposed system as a forward error control (FEC) scheme to improve the performance of BER in OFDM system. Besides, oversampled IFFT and digital filtering techniques are introduced into the system to minimize the out of band radiation (OOBR). In this thesis, we have shown that the proposed system has significantly enhanced the BER performance and minimized the OOBR. However, there are a few trade-offs which affected the overall performance. Hence, we have identified the optimum designed parameters which have resulted in a maximum PAPR reduction and OOBR suppression capability of 9 dB and 52 dB respectively at the cut-off BER of . In comparison to the existing proposed systems, our proposed system can be considered as one of the optimum system as it offers good PAPR reduction as well as OOBR suppression and comparable BER performance at the lowest value of SNR.